Turbulent-layer graphene material and manufacturing method thereof

By using composite particle structure in lithium-ion electrochemical cell units, the primary particles are electrochemically active materials and the envelope is a low-defect messy carbon material, the problem of insufficient cycle stability of the silicon-based anode is solved and a higher cycle life is achieved Stability, energy density and rate performance.

CN119481001APending Publication Date: 2025-02-18NANOGRAF CORP
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411649918.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2019-05-20
Filing Date
2020-05-18
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

The insufficient cyclic stability of the silicon-based anode in lithium-ion electrochemical cell units leads to poor energy density and rate performance, and low Coulomb efficiency due to electrical disconnection caused by volume expansion and unstable solid electrolyte interface film.

Method used

A composite particle structure is adopted, where the primary particles are electrochemically active materials, and the envelope consists of low-defect messy carbon materials. The low-defect messy carbon materials include graphene layers, and the graphene layers partially overlap on the surface of the primary particles to simulate a larger single Piece structure.

Benefits of technology

Through the use of low-defect messy carbon materials, the cycle life stability, energy density and rate performance of lithium-ion electrochemical cell units are significantly improved, and the electrical disconnection caused by volume expansion is reduced, and the Coulomb efficiency is improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119481001A_ABST
    Figure CN119481001A_ABST
Patent Text Reader

Abstract

The invention relates to a disordered graphene material and a manufacturing method thereof. Specifically, the present application provides a disordered layer graphene material having a Raman spectrum, the Raman spectrum having: a D band having a peak intensity (ID) at a wavenumber of between 1330 cm <-1 > and 1360 cm <-1 >; a G band, the peak intensity (IG) of which is at a wavenumber of between 1530 cm <-1 > and 1580 cm <-1 >; and a 2D band having a peak intensity (I2D) at a wavenumber of between 2650 cm <-1 > and 2750 cm <-1 >. The invention also provides a method for manufacturing the disordered graphene material.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] This application relates to a divisional application of an invention patent application with an application date of May 18, 2020, application number 202080043768.0 and invention name “Anode active material containing low-defect turbostratic carbon”. Technical Field

[0002] The present invention relates to anode active materials for electrochemical cells, and more particularly to advanced anode active materials for secondary lithium ion electrochemical cells, the anode active materials comprising composite particles comprising an active material and a low-defect turbostratic carbon material. Background Art

[0003] Lithium (Li) ion electrochemical battery cells generally require materials that can achieve high energy density, high power density and high cycle stability. Li-ion battery cells are generally used in various applications, including consumer electronic devices, wearable computing devices, military mobile devices, satellite communications, spacecraft devices and electric vehicles, and are particularly commonly used in large-scale energy applications such as low-emission electric vehicles, renewable energy power plants and fixed power grids. In addition, lithium-ion battery cells are at the forefront of new generation wireless and portable communication applications. One or more lithium-ion battery cells can be used to configure a battery that serves as a power source for any of these applications. However, this is a surge in the number of applications with higher energy requirements, which is accelerating the research of lithium-ion battery cells with even higher energy density, higher power density, higher charge-discharge capability and longer cycle life. In addition, with the increasing adoption of lithium-ion technology, as applications move to higher current requirements, longer operating time, wider and higher power ranges and smaller form factors, the demand for expanding today's energy and power density is increasing.

[0004] Silicon or silicon alloy anode materials are currently included in most long-term lithium-ion technology adoption roadmaps as a practical means to achieve higher energy and power density. Silicon is a desirable negative electrode active material for lithium-ion electrochemical cell applications, with a theoretical gravimetric capacity of about 4,200 mAh / g and a volumetric capacity of about 9786 mAh / cm when fully lithiated. 3. Silicon is also a promising replacement for current graphite-based anodes because its high lithium storage capacity can exceed 7 times that of graphite. However, market adoption of silicon-based anodes for lithium-ion battery cells is challenged by rapid cycle life degradation, poor charge-discharge rate capability under high power demands, and suboptimal or insufficient coulombic efficiency, all of which can be caused by extreme anode volume changes during charge and discharge (volume expansion of up to 400% has been noted). Cycle life degradation in silicon-based alloys is well understood and can be broken down into two basic mechanisms: (1) electrical disconnection; and (2) an unstable solid electrolyte interface (SEI) that leads to lithium ion depletion and impedance growth. These mechanisms also compromise high rate capability and coulombic efficiency. Due to the large volume changes upon lithiation and delithiation, electrical disconnection occurs with significant volume fluctuations during charge and discharge.

[0005] These large volume changes can lead to pulverization of the silicon particles (stress-induced cracking and fracture) and loss of electrical contact between these active silicon particles. The result is an electrochemical cell with low power capacity and rapid capacity decay. The cracking and fracture introduced in mechanism (1) further deteriorate the battery performance by subsequently promoting mechanism (2) (unstable SEI). Because the cracking and fracture expose new Si surfaces to the electrolyte solvent, further SEI formation occurs, causing the lithiated compounds to be deposited on the new Si surfaces. During the charge / discharge cycle, the insulating SEI layer also thickens, further reducing the capacity and cycle stability of the Si anode and compromising the charge / discharge rate capability and coulombic efficiency.

[0006] The continuous and new growth of SEI layer gradually depletes the available Li + , and due to side reactions with electrolyte solvents and salts, the amount of available electrolyte is also depleted, thereby degrading the overall electrochemical cell performance. Therefore, due to the high ohmic and ionic contributions to polarization by these mechanisms, the use of silicon-based anodes in applications requiring high electrochemical cell charge / discharge rates is severely limited.

[0007] Improving the cycling stability of high specific volume silicon or silicon alloy anodes has been the subject of development for decades. Various approaches have been taken to improve the cycling life stability of silicon anodes, such as, but not limited to, (i) anode particle structure; (ii) particle size control; (iii) particle surface coating or encapsulation; (iv) composite particle composition and / or structure; (v) void space engineering; and (vi) carbon-containing anode composite material mixtures. Due to the favorable physical and electrochemical properties of carbon, the use of carbon variants has become one of the most popular methods for stabilizing the cycling life of silicon alloy anodes. It has been shown that adding carbon to a composite anode material mixture can be used to provide a silicon-based anode with a conductive network and / or matrix that buffers volume expansion during lithiation and delithiation. In addition, it has been shown that nanocarbon materials with one to a few finite atomic layers are particularly beneficial to silicon-based anodes due to their ability to maintain close contact with silicon particles during volume expansion and contraction. Carbon materials such as graphite, graphene, graphene oxide, reduced graphene oxide, exfoliated graphite and graphene, graphene nanosheets or nanoparticles, nanosheets or nanoparticles including flakes comprising one or more graphene layers, carbon nanotubes (CNTs) such as single-walled, double-walled or multi-walled CNTs have all been shown, either individually or in combination, to be beneficial additions to the electrode material mixture.

[0008] It is recognized that the quality of graphene depends largely on the manufacturing and processing conditions during manufacture. For example, the defect density of graphene nanosheets produced by graphene oxidation may be significantly affected by various modifications to the Hummers' production method and subsequent reduction processes. However, the impact of graphene quality on the performance of battery electrodes has not yet been fully characterized. For example, the impact of carbon material defect density and / or lattice stacking on the performance of electrochemical battery cells is essentially lacking. Historically, scanning electron microscopy (SEM) is usually the first option for observing the morphology of Si / graphene composites. However, due to the limitations of SEM imaging, the thickness and number of graphene layers and defect density cannot be properly quantified. Transmission electron microscopy (TEM) has been applied to study the crystal structure of Si / graphene nanocomposites. By adjusting the contrast of the TEM image, the graphene sheet can be separated from the Si / graphene nanocomposite due to the thin thickness and relatively low atomic weight of the graphene sheet, however, it is still impossible to determine the number of layers and limit the defect density. Atomic force microscopy (AFM) has been used to measure the thickness of graphene nanosheets. It has been shown that many fabricated Si / graphene nanocomposites have graphene thickness below 10 nm; however, AFM cannot determine graphene thickness or defect characteristics.

[0009] Therefore, there is a need for an advanced anode material mixture for an electrochemical cell that incorporates a carbon material having defined quality characteristics that favorably impacts the cycling performance of the electrochemical cell. More specifically, there is a need for an advanced silicon-based anode mixture composition that includes low-defect turbostratic carbon that enables cycle life stability, energy density, and rate performance of a lithium-ion electrochemical cell. Summary of the invention

[0010] According to various embodiments of the present disclosure, an electrode material is provided, which includes composite particles, each of which includes: a primary particle, the primary particle includes an electrochemically active material; and a shell, the shell is arranged on the surface of the primary particle, the shell includes turbostratic carbon having a Raman spectrum, the Raman spectrum has: a D band, the peak intensity of the D band (I D ) between 1330cm -1 With 1360cm -1 The peak intensity of the G band is (I G ) between 1530cm -1 With 1580cm -1 and 2D bands, the peak intensity of the 2D bands (I 2D ) between 2650cm -1 With 2750cm -1 In one embodiment, I D / I G The ratio of is in the range of greater than zero to about 1.1, such as greater than zero to about 0.8; and I 2D / I G The ratio is in the range of about 0.4 to about 2, such as about 0.5 to about 2.

[0011] According to various embodiments of the present disclosure, the envelope comprises low-defect turbostratic carbon, the low-defect turbostratic carbon comprising graphene layers, the graphene layers partially overlapping each other on the surface of the primary particle to simulate a larger monolithic structure. In some embodiments, the turbostratic carbon can be in the form of a thin sheet having one or more layers of graphene. In some embodiments, the turbostratic carbon has a low thickness. In some embodiments, the turbostratic carbon is wrinkled, similar to a wrinkled spherical structure. In some embodiments, the turbostratic carbon is wrapped around or bonded to particles of electrode material.

[0012] According to various embodiments of the present disclosure, an active material including a metalloid or metal oxide material is provided.

[0013] According to various embodiments of the present disclosure, an electrochemical cell is provided, comprising a cathode, an anode, and a non-aqueous electrolyte, wherein the non-aqueous electrolyte comprises a lithium salt, and the lithium salt is disposed between the cathode and the anode, wherein the anode comprises low-defect turbostratic carbon. In some embodiments of the electrochemical cell, the low-defect turbostratic carbon is part of a particle structure. In some embodiments of the electrochemical cell, the low-defect turbostratic carbon is part of an electrode material composition. In some embodiments of the electrochemical cell, the low-defect turbostratic carbon is part of an electrode structure.

[0014] According to various embodiments of the present disclosure, methods of making turbostratic carbon and composite particles, electrode material powder compositions, electrochemical cell electrodes, and electrochemical half-cells are provided. These embodiments include low-defect turbostratic carbon.

[0015] Other principal features and advantages of the present invention will become apparent to those skilled in the art upon examination of the following drawings, detailed description and appended claims. BRIEF DESCRIPTION OF THE DRAWINGS

[0016] Figure 1A , 1B and 1C demonstrate Raman spectroscopy for graphite and various graphene-based materials.

[0017] Figure 2 Comparison of Raman spectra of typical carbon materials and low-defect turbostratic carbon I D / I G Bar chart of ratios.

[0018] Figure 3 demonstrated that SiO2 coated with amorphous carbon x Raman spectra of primary particles of electrode active materials.

[0019] Figure 4 The results show that the SiO2 nanostructured ... x Raman spectra of primary particles of electrode active materials.

[0020] Figure 5 The SiO2 layer is encapsulated by low-defect turbostratic carbon. x Raman spectra of primary particles of electrode active materials.

[0021] Fig. 6A is a graph showing the cycle life of exemplary and comparative half-cells according to various embodiments of the present disclosure, and Figure 6B Yes Fig. 6A A table comparing the specific capacity, first coulombic efficiency (CE), and number of cycles to 80% capacity of exemplary and comparative half-cells.

[0022] Figure 7 is a graph showing a voltage polarization comparison of exemplary and comparative full battery cells according to various embodiments of the present disclosure.

[0023] Figure 8 Figure 2 shows the use of the power from the battery at various states of charge (SOC) of exemplary and comparative full battery cells. Figure 7 Plot of the area specific impedance (ASI) curve calculated from the voltage response curve.

[0024] Fig. 9 Figure 2 shows the electrochemical performance of exemplary and comparative full cells after 30 cycles using Figure 7 Figure 2. Voltage response curves calculated from the ASI data.

[0025] Fig.10 is a graph showing the cycle life of exemplary and comparative full battery cells.

[0026] Fig.11 is a diagram illustrating an exemplary hybrid pulse power characterization test scenario.

[0027] Fig.12 It is composed of SiO encapsulated by reduced graphene oxide x Scanning electron microscope (SEM) image of composite particles of primary particles.

[0028] Fig.13 It is composed of SiO encapsulated by low-defect turbostratic carbon. x Scanning electron microscope (SEM) image of composite particles of primary particles. DETAILED DESCRIPTION

[0029] Various embodiments will be described in detail with reference to the accompanying drawings. When appropriate, the same reference numerals will be used throughout the drawings to refer to the same or similar parts. References to specific examples and embodiments are for illustrative purposes and are not intended to limit the scope of the invention or claims.

[0030] It should be understood that when an element or layer is referred to as being "on" or "connected to" another element or layer, the element or layer may be directly on or directly connected to the other element or layer, or there may be intermediate elements or layers. In contrast, when an element is referred to as being "directly on" or "directly connected to" the other element or layer, there are no intermediate elements or layers. It should be understood that for the purposes of this disclosure, "at least one of X, Y, Z" may be interpreted as any combination of only X, only Y, only Z, or two or more items of X, Y, and Z (e.g., XYZ, XYY, YZ, ZZ).

[0031] Where a range of values ​​is provided, it is to be understood that each intermediate value between the upper and lower limits of the range (to one tenth of the unit of the lower limit, unless expressly stated otherwise) and any other stated or intermediate value in the range are encompassed within the present invention. The upper and lower limits of these smaller ranges may be independently included in the smaller ranges and also encompassed within the present invention, subject to any explicit exclusion of the limits within the stated ranges. Where the stated ranges include one or two of the limits, the ranges excluding any one or two of the limits included are also encompassed within the present invention. It is also to be understood that the term "about" may refer to a smaller measurement error, e.g., + / - 5% to 10%.

[0032] Words such as "thereafter," "then," "next," etc. are not necessarily intended to limit the order of the steps; these words may be used to guide the reader through the description of the methods. In addition, any reference to an element in the singular (e.g., using the articles "a," "an," or "the") should not be construed as limiting the element to the singular.

[0033] "Electrode material" is defined as a material that can be configured to be used as an electrode in an electrochemical cell such as a lithium-ion rechargeable battery. "Electrode" is defined as the anode or cathode of an electrochemical cell. "Composite electrode material" is also defined as active material particles combined with particles or flakes of conductive carbon material, the conductive carbon material as a single material of a specific carbon type such as low-defect turbostratic carbon or a combination of more than one specific carbon type. "Electrode material mixture" is defined as a combination of materials such as: material particles (electrochemically active, conductive, composite or a combination thereof), one or more binders, one or more non-crosslinked polymers and / or one or more crosslinked polymers, which are mixed together to form an electrode of an electrochemical cell. "Electrochemically active material", "electrode active material" or "active material" is defined herein as a material that inserts and releases ions such as ions in an electrolyte to store and release electrical potential. The term "insertion and release" can be further understood as ions that are inserted and deintercalated or lithiated and delithiated. Therefore, the process of inserting and releasing ions should also be understood as insertion and deintercalation or lithiated and delithiated. Thus, "active material" or "electrochemically active material" or "active material particles" are defined as materials or particles capable of repeated ion intercalation and deintercalation or lithiation and delithiation.

[0034] A "defect" is defined as any feature that disrupts the symmetry of the hexagonal lattice of carbon atoms in a given carbon sheet. According to this definition, defects can include vacancies, substitutional atoms, edges, grain boundaries, or changes in carbon hybridization. "Hybridization" is the mixing of standard atomic orbitals to form new orbitals, which can be used to describe the bonding of molecules. The mixing of standard atomic orbitals is usually described using the sp 2 and sp3 Track happens.

[0035] Defect density is defined as the number of symmetrically broken features (defects) per given unit area of ​​the carbon plane. This value is usually estimated as the average distance between two defects. D / I G The ratio of is used to approximate the defect density using Raman spectroscopy.

[0036] A "composite particle" may include a primary particle or core comprising an electrochemically active material and an envelope disposed on the surface of the primary particle. The envelope may include turbostratic carbon.

[0037] According to various embodiments of the present disclosure, the primary particles are at least partially encapsulated (e.g., covered) by the envelope. For example, the envelope and / or turbostratic carbon may cover an average of about 10% to about 100% of the surface of each primary particle, such as about 20% to about 90%, about 25% to about 80%, about 30% to about 70%, or about 40% to about 60%.

[0038] An "encapsulation" may be a capsule or shell that at least partially covers, encloses or encapsulates a core material such as at least one primary particle. The primary particle may include an electrochemically active material such as a metalloid or metal oxide material capable of producing a reversible lithium storage capacity. In some embodiments, the encapsulation may have a corrugated morphology. The term "corrugated" is defined as a body or mass that displays a distribution of creases, ripples, folds, wrinkles and ridges. The term "corrugated" is also defined as causing to bend or become curved. The term "morphology" is defined as the structure and one or more features of a surface. Specifically, "morphology" is the structure and features of the outer surface of a particle or macroparticle of an electrode material.

[0039] As defined herein, a "secondary" electrochemical cell is a rechargeable electrochemical cell or battery. "Capacity" is defined herein as a measure of the charge stored by a battery as determined by the mass of the active material contained in the battery, and the capacity represents the maximum energy in ampere-hours (Ah) that can be extracted from the battery at the rated voltage. Capacity can also be defined by the following equation: capacity = energy / voltage or current (A) × time (h). "Energy" is mathematically defined by the following equation: energy = capacity (Ah) × voltage (V). "Specific capacity" is defined herein as the amount of charge that can be delivered per unit mass or per unit volume of active electrode material in a specified time. Specific capacity can be measured in weight units, such as (Ah) / g or volume units, such as (Ah) / cc. Specific capacity is defined by the following mathematical equation: specific capacity (Ah / kg) = capacity (Ah) / mass (kg). "Rate capability" is the ability of an electrochemical cell to receive or deliver a certain amount of energy within a specified period of time. Alternatively, "rate capability" is the maximum continuous or pulse energy that a battery can provide per unit time. "C-rate" is defined herein as a measure of the rate at which a battery is discharged relative to its maximum nominal capacity. For example, a 1C current rate means that the discharge current will discharge the entire battery in 1 hour; a C / 2 current rate will fully discharge the battery cell in 2 hours, and a 2C rate will fully discharge the battery cell in 0.5 hours. "Power" is defined as the time rate of energy transfer measured in Watts (W). Power is the product of the voltage (V) across a battery or battery cell and the current (A) through the battery or battery cell. "C-rate" is mathematically defined as: C-rate (inverse hours) = current (A) / capacity (Ah) or C-rate (inverse hours) = 1 / discharge time (h). Power is defined by the following mathematical equation: power (W) = energy (Wh) / time (h) or power (W) = current (A) × voltage (V). Coulombic efficiency is the efficiency with which charge is transferred within an electrochemical cell. Coulombic efficiency is the ratio of the charge output of a battery to the charge input.

[0040] The present application discloses, among other things, a composite particle comprising an active material and a low-defect turbostratic carbon material additive. A composite electrode material, an electrochemical cell and related processes are further disclosed. The low-defect turbostratic carbon material may include an element of one of the groups consisting of: a particle structure, a particle structure having active material particles as a first component, an electrode material, an electrode, an electrochemical cell and a combination thereof. Low-defect turbostratic carbon provides improved cycle stability and high rate performance compared to other carbon-based materials used in electrochemical cells. Specifically, when low-defect, low-thickness turbostratic graphene and methods thereof are combined as elements of the structure used in electrochemical cells, the low-defect, low-thickness turbostratic graphene and methods thereof provide excellent performance of the electrochemical cell compared to other electrochemical cells using other carbon materials.

[0041] Raman spectroscopy is a technique used to observe vibrational, rotational and other low-frequency modes in a system. Raman spectroscopy is commonly used in chemistry to provide a structural fingerprint by which molecules can be identified. This technique relies on inelastic scattering or Raman scattering of monochromatic light, usually from a laser in the visible, near-infrared or near-ultraviolet range. The laser interacts with molecular vibrations, phonons or other excitations in the system, resulting in an upward or downward shift in the energy of the laser photons. The transfer of energy gives information about the vibrational modes in the system. Therefore, Raman spectroscopy allows the identification and characterization of carbon-based materials ranging from very well-organized carbons such as four-coordinated diamond; to tri-coordinated aromatic carbons such as graphene, nanotubes, nanosheets, nanocones and nanoribbons, down to amorphous carbon. Multi-wavelength Raman spectroscopy has proven to be a very powerful non-destructive tool for the characterization of such carbons. Depending on the material being studied, some specific spectral parameters (e.g., band position, full width at half maximum, relative intensity ratio between two bands) are used to characterize defects.

[0042] sp2 hybridized carbons constitute a broad class of solid phases consisting primarily of elemental carbon, and may be synthetic or naturally occurring. Some non-limiting examples are graphite, graphene, carbon nanotubes, and pyrolytic carbon. These carbons may vary from highly ordered or crystalline solids to completely disordered or amorphous solids, and detailed knowledge of the internal structure and composition of the carbons is extremely important for the scientific and engineering electrochemical cell communities using these materials.

[0043] Interestingly, graphene, which is the basic structural unit for all graphite materials, does not currently have a universal standard material definition because graphene is related to its use in electrochemical cells. Due to the lack of scientific clarity, many forms of graphene or graphene-like materials have been used as electrode additives, including but not limited to single-layer graphene, several layers of graphene, multi-layer graphene, carbon nanobelts and carbon nanosheets, graphene oxide and reduced graphene oxide. Confusingly, all of these materials are often vaguely labeled as graphene in scientific and legal publications despite not meeting the scientific definition of graphene. Because such a standard definition does not exist for an electrochemical cell graphene material or a group of graphene materials, it is currently challenging to select the correct graphene-like carbon material suitable for use as an additive for an electrochemical cell active material mixture.

[0044] Graphene is a material of interest for electrochemical cells because it is a highly effective conductor of electrical and thermal energy. Graphene is also lightweight, chemically inert and flexible. However, because graphene is produced using a variety of processes, the performance results of electrochemical cells vary and are often disappointing. Non-limiting processes for producing graphene include mechanical splitting, epitaxial growth, chemical vapor deposition, and chemical or mechanical exfoliation. Since so many different processes can be used to prepare graphene or graphene-like products, it is expected that graphene can contain many carbon species therein, can have unwanted byproducts as residues in the process, can have potentially harmful structural damage or a combination thereof produced by the process.

[0045] The Raman spectra of all carbon systems show some notable features, regardless of the final structure, whether it is a conjugated polymer or a fullerene. In addition, the carbon system spectra characteristically have a peak in the range of 1000-2000 cm -1 A strong band is shown in the region, besides several other second order modulations appearing in the spectrum. The shape, intensity and position of the peaks in the spectrum allow to distinguish, for example, hard amorphous carbon from carbon nanotubes.

[0046] Figure 1A , 1B Figures 1 and 1C show Raman spectra for graphite and various graphene-based materials. It is well-known that the characteristic peaks of graphite and graphene materials are around 1340 cm -1 、1584cm -1 and 2700cm -1 1340cm -1 The peak at Figure 1C and is characterized by the D band. 1584cm -1 The peak at Figure 1A and 1Cin the spectrum and is characterized by the G band, which is composed of all sp 2 The D band is derived from the vibrational modes represented by the stretching of the C=C bonds of the hybridized carbon atom pairs. The D band originates from the hybridized vibrational modes associated with the graphene edge, and the D band indicates the presence of defects or broken symmetry in the graphene structure. 2700 cm -1 The peak at Figure 1B The 2D bands are characterized as double resonance processes caused by the interaction between stacked graphene layers. The appearance of double peaks at the 2D wavenumbers destroys the symmetry of the peaks and indicates the AB stacking order between graphene planes in graphite and graphite derivatives such as nanosheets. When the AB stacking order of the turbostratic multilayer graphene particles is destroyed, Figure 1B The 2D1 peak shown in is suppressed. The position of the G band and the 2D band is used to determine the number of layers in the material system. Therefore, Raman spectroscopy provides scientific clarity and definition for electrochemical cell carbon material additives, thereby providing a fingerprint for the correct selection of additives as active material electrode compositions. As will be shown below, this definition provides a fingerprint for the low-defect turbostratic carbon of the present application. When used as an additive to an electrochemical cell electrode active material mixture, this low-defect turbostratic carbon provides excellent electrochemical cell performance.

[0047] Figure 2 The invention provides a novel method for preparing a carbon additive (i.e., reduced graphene oxide or amorphous carbon) commonly used in electrode active material mixtures in the prior art compared to the low-defect turbostratic carbon of the present invention. D / I G ratio.

[0048] Reduced graphene oxide (rGO) is a carbon variant that is commonly referred to as graphene in the industry, however, it is unique in its final structure and manufacturing process. Graphene oxide is usually first manufactured using a modified Hermes method, in which a graphite material is oxidized and exfoliated into a monolayer or flake that includes several layers of carbon that may include various functional groups, including but not limited to hydroxyl, epoxide, carbonyl, and carboxyl. These functional groups are then removed by chemical or thermal treatment that converts the insulating graphene oxide into conductive reduced graphene oxide. Reduced graphene oxide is similar to graphene in that reduced graphene oxide consists of a monolayer lattice of carbon atoms, but is different in that reduced graphene oxide has mixed sp2 and sp3 hybridization, residual functional groups, and a generally increased defect density caused by the manufacturing and reduction processes. Reduced graphene oxide is shown in Figure 2 In the first bar, and the I of reduced graphene oxide D / I G The ratio is 0.9, and Figure 4 Shown at 2700cm-1 No 2D resonance is shown nearby.

[0049] Amorphous carbon is commonly used as an additive or surface coating to both the anode and cathode material mixtures of electrochemical cells to enhance electrode conductivity. Typically, amorphous carbon is produced using a chemical vapor deposition (CVD) process in which a hydrocarbon feed gas flows into a sealed container and carbonizes onto the surface of the desired powder material at an elevated temperature. This thermal decomposition process can provide a thin amorphous carbon coating on the order of a few nanometers thick that lacks any sp2 hybridization as found in crystalline graphene-based materials. Amorphous carbon is shown in Figure 2 The third bar of the amorphous carbon D / I G Ratio>1.2.

[0050] Low-defect turbostratic carbon, also known as graphene, includes unique properties resulting from its manufacturing process. A common method of producing this material is through a plasma-based CVD process, in which a hydrocarbon feed gas is fed through an inert gas plasma in the presence of a catalyst that can nucleate graphene-like carbon structures. By controlling the production parameters, carbon materials with several layers and without any AB stacking order between the lattices can be produced. These carbon materials are typically highly ordered sp2 carbon lattices with low defect density.

[0051] The low-defect turbostratic carbon of the present disclosure is shown in Figure 2 The Raman spectrum of the low-defect turbostratic carbon additive of the present application is derived from the intensity ratio of the D band and the G band (I D / I G ) and the intensity ratio of the 2D band and the G band (I 2D / I G ). D ,I 2D and I G Represented by its corresponding integrated intensity. Low I D / I G The ratio indicates a low-defect material. D / I G The ratio is greater than zero and less than or equal to about 1.1, such as less than or equal to about 0.8, as determined by Raman spectroscopy, wherein I G The wave number is between 1530 and 1580 cm -1 In the range between D The wave number is between 1330 and 1360 cm -1and is measured using an incident laser wavelength of 532 nm. In addition, the low-defect turbostratic carbon material of one embodiment of the present disclosure exhibits an I of about 0.4 or greater, such as 0.5 or greater. 2D / I G Ratio. As for I 2D / I G Ratio reference, about 2 I 2D / I G The ratio is usually associated with single-layer graphene. An I of less than about 0.4 2D / I G The ratio is generally associated with bulk graphite composed of a large number of AB stacked graphene layers. Thus, for the low-defect turbostratic carbon materials of the present disclosure, an I of about 0.4 or greater, such as about 0.5 or greater 2D / I G The ratio indicates a low layer count of ≤ 10. Low-defect turbostratic carbon materials with low layer counts further lack AB stacking order (i.e., turbostratic) between graphene layers. The turbostratic nature of these graphene planes or the lack of AB stacking is indicated by I 2D The symmetry of the peaks indicates that the symmetry of the 2D peaks distinguishes turbostratic graphene layered materials from AB stacked graphene layered materials and indicates rotational stacking disorder versus layered stacking order.

[0052] Carbon materials with high AB stacking order will still show 2D peaks, however, these 2D peaks show double peaks that destroy the symmetry of the peaks. This symmetry destruction is shown in both a few layers of AB stacked graphene or perhaps multiple layers of graphite. Therefore, when selecting graphene or graphene-based additives, the 2D peak (which is a very strong indicator of stacking order, regardless of the number of graphene layers present in the material) is of great significance. The rotational disorder of the stacking in the low-defect turbostratic carbon disclosed in the present invention distinguishes itself from all other graphene or graphene-based additives used so far, because the rotational disorder of the low-defect turbostratic carbon stacking of the present application provides flexibility for the carbon-based particles of the present application, which enables these carbon-based particles to provide and maintain contact with the active primary particles of the composite particles of the electrodes of the electrochemical cell. The result is an electrochemical cell with increased cycle life, better cycle life stability, enhanced energy density and excellent high rate performance.

[0053] When silicon and silicon alloys are incorporated into electrodes of electrochemical cells, they significantly increase the capacity of the battery. Silicon and silicon alloys are typically incorporated into electrodes that include graphite, graphene, or other carbon-based active materials. Examples of electrodes that include carbon-based materials and silicon are provided in U.S. Patents 8,551,650, 8,778,538, and 9,728,773 to Kung et al. and U.S. Patents 10,135,059 and 10,135,063 to Huang et al., the entire contents of which are fully incorporated herein by reference.

[0054] One embodiment of the material of the present invention includes composite particles. The composite particles may include at least one primary particle (i.e., active material particle), wherein the primary particle includes a metalloid or metal oxide material. The primary particle may be an anode active material particle. The primary particle may have an average particle size in the range of about 1 μm to about 15 μm. Alternatively, the average particle size of the primary particle may be less than about 1 μm. The primary particle may have an average particle size in the range of about 0.5 μm. 2 / g to about 50m 2 In an embodiment, the metal oxide of the primary particles comprises silicon oxide (SiO x ), wherein x is in the range of about 0.1 to about 1.3, such as 0.8 to 1.2, including 0.9 to 1.1. In an embodiment, the primary particle comprises lithium-containing silicon oxide (Li z SiO x ), wherein x is in the range of about 0.1 to about 1.3 and z is in the range of greater than zero to about 4.0. Some embodiments may include a low-defect turbostratic carbon material that surrounds, encapsulates, interweaves, is dispersed around, or is integrated and / or agglomerated with primary particles.

[0055] The composite particle may further include an envelope disposed on the surface of the primary particle and including low-defect turbostratic carbon. The envelope or low-defect turbostratic carbon may at least partially cover or encapsulate the primary particle. The envelope may include low-defect turbostratic carbon in the form of a sheet, the low-defect turbostratic carbon including one to about 10 sheets of graphene, graphene oxide or reduced graphene oxide. In some embodiments, at least 90%, such as 90% to about 100%, of the layer or sheet may be formed by graphene.

[0056] In an embodiment, the average particle size of the composite particles may be ≤ 10 μm. In an embodiment, the average particle size may be about 1 μm or less. In an embodiment, the composite particles may have an average particle size in a range of about 0.5 μm to about 15 μm, about 0.5 μm to about 5 μm, about 0.5 μm to about 2 μm, or about 0.5 μm to about 1.5 μm. The composite particles may be included in an active electrode material, such as an active anode electrode material.

[0057] Composite particles can be formed by combining electrochemically active carbon materials and low-defect turbostratic carbon materials in a dry weight ratio between 7:3 and 99:1. The original active material and the carbon material are first suspended in a polar liquid solvent such as water or ethanol by high shear mixing or ultrasonic treatment. The important advantage of low-defect turbostratic carbon is that it can be suspended in a polar solvent with a high solid loading, making it suitable for low-cost wet chemical processing. Graphene oxide is a possible option, because graphene oxide has various oxygen-containing functional groups. The oxygen-containing functional groups are connected to the carbon lattice and enable graphene oxide to be suspended in various polar solvents with a low solid loading. Other types of carbon additives generally lack suspension ability and therefore must be dry processed or grown on a matrix material. Suspensions of some materials can also be promoted by using surfactants such as polyvinyl pyrrolidone (PVP). Importantly, when compared to other carbon additives, the high conductivity achieved by the low-defect turbostratic structure allows lower ratios of material (<90:10 and as low as 99:1) to be mixed with the electrochemically active material to achieve comparable conductivity enhancement.

[0058] Once the raw material suspension is made, it is then atomized and dried in a vacuum heating chamber to force the suspended solids into close contact. Depending on the final powder particle requirements, the process parameters may vary. For example, spherical composite particles that are wrinkled by atomizing droplets and then drying them quickly in a heating chamber. For example, an atomizer atomizes the raw material suspension to form aerosol droplets. The atomization step requires sufficient spray parameters to allow the particles within the droplets to become ordered before aerosol evaporation begins. For turbostratic carbon materials, the particles within the droplets migrate to the surface of the droplets to form a hollow envelope of spheres when dried. If the droplets contain only turbostratic carbon, the envelope can be used as a conductive additive for electrode materials. The envelope minimizes particle aggregation and agglomeration because this structure overcomes the strong inter-particle van der Waals attraction that causes the carbon material sheets to restack, which complicates solution processability and reduces particle accessible surface area. This structure is also stable against unfolding or folding.

[0059] If the droplets contain both carbon-based materials and electrochemically active materials, the electrochemically active material may be located in the center of the droplets, while the carbon-based material may be located at the surface of the droplets. Ordered aerosol droplets flowing through a preheating furnace allow carbon-based material particles to be positioned, aggregated, and flattened at the surface of the droplets, and then ready to encapsulate the electrochemically active material centrally located within the droplets. Aggregation and flattening occur as the droplets shrink due to evaporation during drying, and encapsulation occurs simultaneously. The turbostratic carbon is then completely concentrated around the internal cargo of the electrochemically active material, forming an initial spherical structure. As the droplets continue to shrink, curvature is introduced, followed by significant wrinkles, bends, and twisted edges. Ultimately, the flakes / sheets are isotropically compressed by capillary forces, and the flakes / sheets are completely wrinkled, thereby transforming into wrinkled balls with many wrinkles, bends, and twists that do not relax over time. This structural transformation of carbon-based particles to form an envelope surrounding the core material is important for the integrity of the particle, as any relaxation of the turbostratic carbon envelope will reintroduce the internal particle cargo to electrolyte exposure and the effects of fracture and unstable SEI formation.

[0060] The preparation of the dispersion to be atomized is also important because it is intended to produce heterogeneous droplets including solid particles suspended in a droplet-forming liquid. The droplet-forming liquid should be a liquid in which the integrity of the particles is maintained so that the particles will be isotropically compressed and plastically deformed to form approximately spherical particles that are like crumpled paper balls. In addition, it is important to maintain the droplets in the furnace carrier gas for a period of time (that is, until complete evaporation is achieved) in order to complete the crumpled spherical envelope and encapsulation of the internal cargo. In this way, the aerosol-assisted evaporative capillary compression process forms particles similar to hollow spheres that resist aggregation, exhibit excellent processability, and can be used as conductive additives or can alternatively encapsulate electrochemically active internal cargo for use in electrodes of electrochemical cells.

[0061] Once the droplet evaporation is complete, the dry powder is collected. After collection, the dry powder can be heat treated in an inert atmosphere such as argon to carbonize any remaining surfactant or dispersant. The resulting dry powder can then be classified by sieving or filtering to achieve the desired particle size distribution for a given application.

[0062] One embodiment of the material of the present invention includes an active electrode material, the active electrode material including a metalloid or metal oxide active material. The active material may include an active anode material, wherein the active anode material includes a metalloid or metal oxide material. The active material may further include a carbon-based material additive. The carbon-based material additive may include a low-defect turbostratic carbon-based material. In some embodiments, the low-defect turbostratic carbon includes graphene flakes, which are part of a structure including a continuous network for a composite electrode material, the composite electrode material including: (a) a mechanical support for the active electrode material; and (b) a conductive path for the active electrode material. The mechanical support assists the conductive path by providing and maintaining contact between the active electrode material and the carbon-based material additive during the cycling of the electrochemical cell.

[0063] One embodiment of the material of the present invention includes an electrode comprising a metalloid or metal oxide active material. The electrode may alternatively include a carbon-based material. The electrode may include both a metalloid or metal oxide material and a carbon-based material. The carbon-based material may contain low-defect turbostratic carbon, which may be present at a wrinkled sheet comprising one or more sheets of graphene. The electrode may include: composite particles; electrochemically active particles; conductive particles; electrically insulating particles; chemically active particles; intercalation / deintercalation particles; carbon-based particles; metalloid or metal oxide particles; alloy particles; wrinkled particles; agglomerated particles; and combinations thereof. In some embodiments, the diameter of the composite particles may be ≤1 μm on average. In some embodiments, the composite particles may have a diameter in the range of about 1 μm to about 15 μm. The electrode may include turbostratic carbon sheets or sheets that are partially overlapped to simulate a larger-sized monolithic structure. In some embodiments, the sheet has more than one or more layers of graphene-based materials. In some embodiments, the sheet size of the sheet may be ≤15 μm on average. In some embodiments, the sheet size of the sheet may be ≤1 μm on average. In some embodiments, the turbostratic carbon-based material flakes may have a low thickness. In some embodiments, the low thickness of the turbostratic carbon-based material flakes may be ≤1 μm on average. In some embodiments, the low thickness of the turbostratic carbon-based material flakes may be ≤100 nm on average. In some embodiments, the turbostratic carbon-based material flakes are wound around, woven / interwoven through, or bonded to at least some of the particles of the electrode material in the electrode. The electrode may further include one of one or more binders, one or more non-crosslinked polymers, one or more crosslinked polymers, and combinations thereof. The electrode may be an anode, a cathode, or one of both.

[0064] Low-defect turbostratic carbon materials are advantageous for electrode slurry coating techniques. The electrode may include a low-defect turbostratic carbon material and optionally a binder and an additional electrochemically active material. The electrode may include one of the following: (1) only one or more low-defect turbostratic carbon materials; (2) one or more low-defect turbostratic carbon materials and other carbon-based material additives, such as carbon black, graphite, graphite oxide, graphene, exfoliated graphite or graphene, graphene oxide, rGO, partially reduced GO, carbon nanotubes (CNTs) such as single-walled, double-armed or multi-walled CNTs, graphene flakes, nanosheets or nanoparticles, nanosheets or nanoparticles including graphene sheets or several graphene sheets, and combinations thereof; (3) one or more low-defect turbostratic carbon materials and one or more cathode active materials, such as metal oxides, lithiated metal oxides, metal fluorides, lithiated metal fluorides or combinations thereof; sulfur, lithium sulfide, metal fluorides, lithium metal fluorides, lithium metal phosphates and lithium metal silicates, wherein the metal may include transition metals such as iron, manganese, cobalt, nickel, copper, vanadium, chromium and / or non-transition metals such as bismuth and combinations thereof; lithium-rich cathode active electrode materials, which may include magnesium, strontium, barium, cadmium, zinc, aluminum, gallium, boron, zirconium, titanium, calcium, selenium, yttrium, niobium, chromium, iron, vanadium, lithium and combinations thereof; and (4) one or more low-defect carbon-based materials and one or more anode active materials including an anode active component, wherein the anode component includes a metalloid or metal oxide material.

[0065] The electrode may include a composite material mixture that can provide 100% anode lithium capacity or may be mixed with other lithium active materials such as graphite, graphite oxide, graphene, graphene oxide, rGO and partially reduced GO in a 0-100% mixture. If the electrode includes a binder for holding the electrode material together, the binder may include a polymer material such as polyacrylic acid or polyvinylidene fluoride (PVDF), carboxymethyl cellulose (CMC), styrene-butadiene rubber (SBR), CMC / SBR, polyacrylic acid (PAA), lithium polyacrylate (LiPAA) or a combination thereof. The electrode material components are then mixed in a polar solvent such as water or N-methyl-2-pyrrolidone (NMP) at a solid loading ranging from about 20wt% to about 60wt% to form an electrode slurry. Mixing is typically achieved with a planetary mixer and high shear dispersion blades. The electrode slurry is then coated on a metal substrate (usually copper or aluminum) with an appropriate mass loading to balance the lithium capacity of the anode with the lithium capacity of the selected cathode. Coating can be performed using a variety of equipment, such as a doctor blade, comma coater, gravure coater, and slot die coater. After coating, the slurry is dried under forced air between room temperature and about 120°C. Before the battery cell is assembled, the final electrode processing step includes pressing the electrode to reduce internal porosity and cutting into appropriate geometric shapes. Typical pressing densities can range from about 1.0 g / cc to about 1.7 g / cc, depending on the composition of the electrode and the target application.

[0066] One embodiment of the material of the present invention includes an electrochemical cell comprising an anode, a cathode, and a non-aqueous electrolyte comprising a lithium salt. The anode comprises a metalloid or metal oxide material. The anode further comprises a low-defect turbostratic carbon material. The anode may include composite particles. The composite particles may further include a corrugated spherical structure, wherein the corrugated structure comprises a low-defect turbostratic carbon material encapsulating a metalloid or metal oxide material in its core. The anode may alternatively include an anode material mixture having particles comprising a metalloid or metal oxide material and particles comprising a turbostratic carbon material. The turbostratic carbon material may include a low-defect turbostratic carbon sheet, which is entangled and / or bonded to at least some of the primary particles of the primary particles comprising the metalloid or metal oxide material. The cathode may include a carbon-based material. In addition to conventional carbon-based materials used in the cathode electrode of an electrochemical cell, it is contemplated that the low-defect turbostratic carbon material of the present application may also be used as an additive to the cathode electrode of an electrochemical cell.

[0067] The construction of the electrochemical cell involves the pairing of a coated anode substrate and a coated cathode substrate electrically isolated from each other by a polymer and / or ceramic electrical insulating separator. The electrode assembly is hermetically sealed in a housing, which may have a variety of structures, such as, but not limited to, a button cell, a soft pack cell, or a can cell, and contains a non-aqueous ion-conductive electrolyte operatively associated with the anode and cathode. The electrolyte is composed of an inorganic salt dissolved in a non-aqueous solvent and more preferably an alkali metal salt dissolved in a mixture of a low viscosity solvent containing an organic ester, an ether, and a dialkyl carbonate and a high conductivity solvent containing a cyclic carbonate, a cyclic ester, and a cyclic amide. Non-limiting examples of electrolytes may include an organic solvent containing lithium hexafluorophosphate (LiPF6) or a lithium bis(fluorosulfonyl)imide (LiFSi) salt, the organic solvent comprising one of the following: ethylene carbonate (EC), diethyl carbonate (DEC), dimethyl carbonate (DMC), fluoroethylene carbonate (FEC), or a combination thereof. Additional solvents that can be used in embodiments of the present invention include dialkyl carbonates such as tetrahydrofuran (THF), methyl acetate (MA), diethylene glycol dimethyl ether, triethylene glycol dimethyl ether, tetraethylene glycol dimethyl ether, 1,2-dimethoxyethane (DME), 1,2-diethoxyethane (DEE), 1-ethoxy-2-methoxyethane (EME), ethyl methyl carbonate, methyl propyl carbonate, ethyl propyl carbonate, dipropyl carbonate, and combinations thereof. Also potentially useful high dielectric constant solvents include cyclic carbonates, cyclic esters, and cyclic amides such as propylene carbonate (PC), butylene carbonate, acetonitrile, dimethyl sulfoxide, dimethylformamide, dimethylacetamide, γ-valerolactone, γ-butyrolactone (GBL), N-methyl-2-pyrrolidone (NMP), and combinations thereof. The electrolyte acts as a medium for lithium ions to migrate between the anode and cathode during the electrochemical reaction of the battery cell, particularly during the discharge and recharge of the battery cell. Electrochemical cells may also have positive and negative terminals and / or contact structures.

[0068] In each of the above embodiments, the metalloid or metal oxide material is selected from the group consisting of: silicon (Si), germanium (Ge), tin (Sn), lead (Pb), lithium (Li), antimony (Sb), bismuth (Bi), zinc (Zn), aluminum (Al), silver (Ag), gallium (Ga), magnesium (Mg), carbon (C) and cadmium (Cd); their alloys, their intermetallic compounds, their oxides or any combination thereof.

[0069] Figure 3-5 A SiO2 comprising a carbon material encapsulated or coated with a carbon material is presented. x Raman spectra of active material mixtures of primary particles. Figure 3 It is composed of SiO coated with an amorphous carbon material. x Raman spectra of active material mixtures of primary particles. Figure 4It is composed of SiO encapsulated by rGO x Raman spectra of active material mixtures of primary particles. Figure 5 It is composed of SiO encapsulated by low-defect turbostratic carbon. x Raman spectra of the active material mixture of the primary particles. Each spectrum is due to the layer thickness (wavelength 2700 cm -1 The size, shape and position of the surrounding 2D peaks) and disorder (wavelength 1340 cm -1 The size of the surrounding D peak) varies.

[0070] Raman analysis sample preparation involves taking a small aliquot of powder, such as active material powder, composite material powder, carbon material powder, and placing these powders individually in clean glass bottles. The sample powder is rinsed with methanol. The powder / methanol solution is then briefly vortexed and sonicated for about 10 minutes. The suspension is then transferred to a microscope slide with a micropipette. The slide is then allowed to air dry completely before analysis.

[0071] The Raman spectroscopy analysis of the present application was performed using confocal Raman spectroscopy on a Bruker Senterra Raman system under the following test conditions: 532 nm laser, 0.02 mW, 50X objective, 90 s integration time, using a 50×1000 μm aperture and 9–18 cm -1 3 co-additions (3 Raman spectroscopy sample runs) of resolution. As a reference point, the D band is not active in Raman scattering in a perfect crystal. The D band becomes Raman active in defective graphitic materials due to defect-induced double resonance Raman scattering processes involving π-π electronic transitions. The intensity of the D band relative to the G band increases with the amount of disorder. D / I G The intensity ratio of can thus be used to characterize the graphene material.

[0072] Figure 3 The intensity ratio of the D band and the G band of amorphous carbon is shown Figure 4 The D band and G band of reduced graphene oxide (rGO) or Figure 5 The intensities of the D and G bands of the turbostratic carbon are higher. Amorphous carbon also shows significantly higher I D / I GRatio (1.25). The suppression intensity of the G band of amorphous carbon, compared to the suppression intensity of the D band of amorphous carbon, reflects the lack of crystallinity in its carbon structure (also known as its graphitic nature). The D peak intensity is higher than the G peak intensity due to the large number of defects in the amorphous carbon network. Therefore, compared with more crystalline carbons such as graphene, graphene oxide and rGO, the amorphous carbon spectrum shows low crystallinity and much higher disorder in its graphitic network. In addition, the intensity of its D peak compared to the G peak of rGO and its I D / I G The ratio (almost 2X) is higher than the intensity of D and G peaks of turbostratic carbon and I D / I G The ratio is higher, which indicates that rGO has more defects than the turbostratic carbon of the present application.

[0073] The following table provides Figures 3 to 5 Details of the Raman spectrum.

[0074]

[0075] A careful inspection of these spectra shows that the D band becomes broader as disorder increases and the relative intensities of the bands change. For the amorphous carbon coated sample, the high intensity (6194.8) and broad D peak indicate the presence of a large number of defects. The D peak intensity (6194.8) is lower than the G peak intensity (4908.2) indicating a lack of crystallinity. The D peak intensity (9115.5) and G peak intensity (10033.3) of the rGO encapsulated sample are quite similar. However, it is worth noting that the D peak intensity of the rGO sample (9115.5) is significantly higher than the D peak intensity of the turbostratic carbon sample (2915.3), indicating that the defect density of the rGO sample is significantly higher than that of the turbostratic carbon sample. It is also worth noting that the G bands of the amorphous carbon and rGO samples extend from wavelengths of 1584cm to 2915.3, respectively. -1 Shift right to a wavelength of 1589.4 cm -1 and 1597.82cm -1 , while the G band of the turbostratic carbon sample is at 1581.32 cm -1 Slightly at a wavelength of 1584cm -1 Importantly, unlike the amorphous carbon and rGO samples, the turbostratic carbon (in this case, graphene samples) did not show much, if any, positional displacement, reflecting the low defect content therein and, therefore, the turbostratic carbon samples most closely resembled a nearly "perfect" turbostratic carbon material.

[0076] Fig. 6A A comparison includes an anode (the anode includes SiO encapsulated by low-defect turbostratic carbon xAn exemplary composite particle of a primary particle, wherein x is about 0.6) and an exemplary half-cell comprising an anode (the anode comprising SiO encapsulated by rGO x A graph of the cycle life of comparative half-cells of comparative composite particles of primary particles). Figure 6B is a graph comparing the specific capacity, first coulombic efficiency (CE), and percent capacity retained to 80% capacity of exemplary and comparative half-cells.

[0077] refer to Fig. 6A and 6B , exemplary and comparative composite particles of SiO x The ratio of Li:carbon was about 80:20. The anode was formed by coating the corresponding anode material suspension onto a substrate. The active material:conductive additive:LiPAA binder ratio of the corresponding electrode composition was 75:5:20. The electrodes were punched and calendered to a pressed density of 1.1 g / cc and built into electrochemical test cells using lithium or NMC 523 counter electrodes, polypropylene separators, and 1.0M LiPF6 EC:DEC (3:7) electrolyte with 20% FEC additive. Figure 6B The table shows that the first coulombic efficiency of the exemplary half-cell comprising a low-defect turbostratic carbon anode material is 3% higher than that of the comparative half-cell comprising a comparative anode material including rGO, which demonstrates that there is less irreversible loss of lithium during formation. In addition, the exemplary half-cell retains 98% of its capacity when cycled to 80% of its design capacity, while the comparative half-cell retains only 57% of its capacity when cycled to 80% of its design capacity. Thus, the exemplary half-cell exhibits approximately 42% more capacity retention than the comparative half-cell, which demonstrates that the low-defect turbostratic carbon material has a positive impact on cycling stability.

[0078] Figure 7-9 are graphs showing voltage polarization, area specific impedance (ASI) curves, and high speed capacity comparison of data for exemplary and comparative full battery cells, respectively. Figure 8 and 9 The ASI in is calculated using a standardized hybrid pulse power characterization (HPPC) technique developed by the US Council of Automotive Research for battery technology for electric vehicles. The measured value of ASI is a complex combination of internal resistance of the battery, which is produced by physical processes occurring at different lengths and time scales. Therefore, the measured value ASI is a function of several factors, including: state of charge (SOC), pulse length, current density, C-rate, particle size, lithium diffusion length, and specific media. The combination of these factors is measured by the voltage response (polarization) to a charge or discharge current pulse, as defined by the following equation:

[0079]

[0080] Where V = the measured voltage of the battery cell,

[0081] I = applied current,

[0082] t0 = the time immediately before the pulse current is applied, and

[0083] t1 = time immediately before the application of pulse current is terminated.

[0084] Exemplary and comparative electrochemical full cells were constructed, keeping all components and feedstocks constant, except for an exemplary cell comprising an exemplary anode material comprising turbostratic carbon and a comparative cell comprising a comparative anode material comprising rGO. Figure 8 Shown for Figure 7 Results of the HPPC tests performed indicate that at the same SOC, the ASI of the exemplary battery cell is lower than the ASI of the comparative battery cell at all SOCs. Figure 8 , ASI is used in various SOCs from Figure 7 The effect is attributed to the reduced impedance contribution of the turbostratic carbon additive to the overall cell polarization due to its lower defect rate within the turbostratic carbon lattice. This trend continues as the test cell is cycled to 100% discharge.

[0085] Fig. 9 It is shown that after cycling the full cell between 4.2V-2.8V for 30 cycles using a C / 2 constant current constant voltage (CCCV) charging protocol and a 2C discharge protocol, the ASI increase of the comparative cell is greater than the ASI increase of the exemplary cell. Fig. 9 , ASI was tested after 30 electrochemical cycles using Figure 7 The ASI is calculated from the voltage response curve of the battery. This increase in ASI indicates that the comparative battery cell has lower cycling stability and greater resistance accumulation when repeatedly cycled than the exemplary battery cell. In addition, as the number of cycles increases, the cycling stability of the comparative battery cell decreases and its resistance increases.

[0086] Fig.10 is a graph showing the cycle life of exemplary and comparative full battery cells according to various embodiments of the present disclosure. Fig.11The exemplary and comparative full battery cells are 2032 button-type battery cells, each of which comprises: an NMC cathode; a polypropylene separator; an electrolyte comprising EC:DEC:DMC (1:1:1) containing 1.0M LiPF6 and 20% FEC; and an anode comprising 60% SiO x , 20% graphite, 5% conductive additive and 15% PAA binder. The SiO of the exemplary cell was entangled in turbostratic carbon, and the anode of the comparative cell was coated with amorphous carbon deposited by CVD.

[0087] like Fig.10 As shown, the exemplary battery cell shows better initial capacity than the comparative battery cell at a 2C discharge rate. The exemplary battery cell also shows improved cycling stability compared to the comparative battery cell.

[0088] Fig.11 is a graph showing current application during the HPPC test protocol. Fig.11 The sequence of rest periods, pulse profiles, and discharge segments is shown. The purpose of this test is to determine the discharge pulse (5C rate) and charge pulse (3.75C) power capabilities at each 10% capacity increment relative to the maximum operating capacity of a given battery cell. Between each pair of discharge and regeneration (charging) pulses, the device is discharged to the next 10% increment based on operating capacity using a C / 3 rate. The HPPC test begins with the device device using the manufacturer's recommended program until Vmax, followed by a default rest period (usually 1 hour). The test is typically programmed so that 10% of the operating capacity is removed in each test segment, including the operating capacity removed by the pulse profile itself. The HPPC profile is performed immediately, followed by a discharge to the next 10% increment of rated capacity at C / 3 and a default rest is performed. This sequence is repeated until a final profile that removes 90% or close to 90% of the operating capacity is removed. The test terminates with the device discharged to Vmin0 at a C / 3 rate and a final default rest.

[0089] Fig.12 It includes 80:20SiO x :rGO wt% ratio of SiO x Scanning electron microscopy (SEM) images of primary particles and comparative composite particles with aggregates of wrinkled rGO sheets. Visible are SiO randomly distributed around the wrinkled rGO sheets (region 2). xSmall grape-like clusters of particles (area 1). The composite particles shown as derived from the image micrometer markers are larger than 5 μm and exhibit morphological changes that may otherwise adversely affect the electrochemical properties of the powders comprising these particles. Various SiOx clusters encapsulated by the wrinkles of the rGO sheets are shown in the SEM images. Also shown and of particular importance to the resulting electrochemical properties of the powders is the particle morphology of the wrinkled rGO sheets and the SiO x There are many void spaces with poor contact (i.e., lack of intimate contact) between the primary particles (region 3 is an example). In addition, the SEM images show that the composite particles also exhibit an excess of SiO x The wrinkled rGO sheets of the clusters (area 4 is an example). This change in composite particle morphology is relative to the average SiO x The primary particles are selected as a result of large lateral rGO sheet sizes, thereby allowing the excess rGO to fold upon itself, thereby producing a SiO x Composite particles covered with excess or insufficient rGO of primary particles. As previously disclosed, SiOx primary particles can be submicron (less than 1 μm) or can have an average particle size in the range of about 1 μm to about 15 μm. Therefore, when compared to primary particles encapsulated with low-defect turbostratic carbon of the present application, in addition to the higher defect density of the rGO (i.e., as determined by Raman spectroscopy, I D / I G ratio>0.8), these morphological changes leading to lack of intimate contact and distributed contact with SiOx particles further contribute to the reduced effectiveness of rGO in providing conductivity to SiOx primary particles.

[0090] Fig.13 It is composed of 80:20SiO x : Carbon wt% ratio of SiO encapsulated by low-defect turbostratic carbon sheets x SEM image of an exemplary composite particle of primary particles. Visible are clustered Si alloy primary particles encapsulated by and in intimate contact with low defect carbon sheets forming discrete, nearly spherical composite particles (Region 1 is an example of one of these particles). The particle size of the composite particles as shown, derived from the image micron markers, is less than 5 μm. These composite particles have a defined structural fingerprint that exhibits an I greater than zero and less than or equal to about 1.1 as determined by Raman spectroscopy performed at a 532 nm laser excitation wavelength. D / I G ratio and an I of about 0.4 to about 2.0 2D / I G Ratio, where I D / I G A ratio of ≤1.1 indicates low defects, and a ratio of about 0.4 or greater indicates low defects. 2D / IG The ratio indicates a low sheet count of about 10 sheets or less. In addition, a 2D band that exhibits a single-peak profile symmetrical about its peak and an intensity higher than that of its G band indicates turbostraticity and lack of AB stacking between sheets. The low sheet count and lack of AB stacking between sheets of low-defect turbostratic carbon materials produce a mossymosaic-like structure on the surface of these composite particles (region 2 is an example). The low sheet count and lack of AB stacking order make the composite particles flexible, making the SiO x Intimate contact is created and maintained between the primary particles and the encapsulated low-defect turbostratic carbon material. Intimate contact between the primary particles and the carbon can be observed in the SEM images. It is noteworthy that the uniqueness of the low-defect turbostratic carbon material is that it lacks the excessive folds or wrinkles present in rGO particles.

[0091] Various electrochemical tests were performed, all of which indicated that low-defect turbostratic carbon exhibited better performance than reduced graphene oxide. The winding, mixing, coating or encapsulation of silicon alloy active materials with low-defect turbostratic carbon additives provides a flexible and conductive matrix to ensure that the individual particles remain in electrical contact after the significant volume changes associated with lithiation / delithiation of the active material. The electrochemical performance of silicon alloy anode materials in terms of cycling stability and high rate discharge can be maximized by optimizing the defect characteristics of the carbon additive and appropriately incorporating it onto the surface of the silicon alloy active particles. In particular, low defect density is necessary to enhance the intrinsic conductivity of the carbon material and is comparable to SiO x The intimate and uniform contact of the active materials ensures that this enhanced conductivity participates in the charge transfer process upon lithium insertion and extraction.

[0092] Although the foregoing refers to certain preferred embodiments, it should be understood that the present invention is not limited thereto. It will be appreciated by those skilled in the art that various modifications may be made to the disclosed embodiments, and these modifications are intended to be within the scope of the present invention. All publications, patent applications, and patents cited herein are incorporated herein by reference in their entirety.

Claims

1. A turbostratic graphene material having a Raman spectrum, wherein the Raman spectrum has: D band, the peak intensity of the D band (I D ) between 1330cm -1 With 1360cm -1 At the wave number between G band, the peak intensity of the G band (I G ) between 1530cm -1 With 1580cm -1 At wave numbers between ; and 2D spectral band, the peak intensity (I 2D ) between 2650cm -1 With 2750cm -1 The number of waves between.

2. The turbostratic carbon according to claim 1, wherein: I D / I G The ratio of is in the range of greater than zero to about 1.1; and I 2D / I G The ratio is in the range of about 0.4 to about 2.

3. The turbostratic carbon according to claim 2, wherein: I D / I G The ratio of is in the range of greater than zero to about 0.8; and I 2D / I G The ratio is in the range of about 0.5 to about 2.

4. The turbostratic carbon according to claim 3, wherein: I D / I G The ratio is in the range of 0.3 to 0.7; and I 2D / I G The ratio is in the range of 0.8 to 1.

2.

5. The turbostratic carbon according to claim 1, wherein: I D At about 1340cm -1 The wave number of I G At about 1584cm -1 and I 2D At about 2700cm -1 The wave number of .

6. A method for preparing the turbostratic carbon according to claim 1, the method comprising: suspending a solid carbon material in a polar liquid solvent to form a suspension; atomizing the suspension; as well as The atomized suspension is dried to force the suspended solid carbon material into intimate contact so as to form a hollow envelope of a wrinkled sphere.

Citation Information

Patent Citations

  • Crumpled particles, methods of synthesizing same and applications using same

    US10135059B2

  • Crumpled graphene-encapsulated nanostructures and lithium ion battery anodes made therefrom

    US10135063B2

  • Graphene materials having randomly distributed two-dimensional structural defects

    US8551650B2

  • Electrode material comprising graphene-composite materials in a graphite network

    US8778538B2

  • Electrode material comprising graphene-composite materials in a graphite network

    US9728773B2